The MaDo real-life study of dose adjustment of allergen immunotherapy liquid formulations in an indication of respiratory allergic disease: Reasons, practices, and outcomes - Thétis-Soulié, Marguerite; Hosotte, Maxime; Grozelier, Isabelle; Baillez, Claire; Scurati, Silvia; Mercier, Valérie (Frontiers in Allergy, 2022)
Sublingual allergen immunotherapy (SLIT) is a safe, effective disease-modifying treatment for respiratory allergies. The function and responsiveness of the immune system components underlying the effects of SLIT may vary from one patient to another. Furthermore, the severity of the symptoms over time, due to changes in allergen exposure, effector cell responsiveness, and cell signaling. Hence, the allergen dose provided through SLIT can be fine-tuned to establish and maintain an optimal balance between effectiveness and tolerability. The objective of MaDo, a retrospective, observational, cross-sectional, real-life study, was to describe and understand dose adjustments of SLIT liquid formulations in France. Physicians described their patients via an anonymous case report form (CRF). The main patient inclusion criteria were age 5 years or over, at least one confirmed IgE-driven respiratory allergy and treatment for at least 2 years with one or more SLIT. A representative sample of 33 physicians participated in the study. The physicians’ main stated reasons for dose adjustment were adverse events (for 90.9% of the physicians), treatment effectiveness (60.6%), sensitivity to the allergen (42.4%) and other characteristics (30.3%: mainly symptom severity, allergen, and asthma). 392 CRFs (mean ± standard deviation patient age: 27.8 ± 17.5; polyallergy: 30.9%) were analyzed. Respectively 53.6%, 25.8%, 15.3%, and 8.7% of the patients received house dust mite, grass, birch and cypress pollen SLIT. Dose adjustments were noted in 258 (65.8%) patients (at the start of maintenance phase for 101 patients (39.2%)) and later for 247 (95.7%)). Dose adjustment was not linked to sex, age, or number of allergens administered. All measures of disease severity decreased significantly during SLIT. The mean AR symptom score decreased to a clinically relevant extent from 7.6 at SLIT initiation to 2.4 at last follow-up, and the mean asthma symptom score from 5.0 to 1.3. In France, dose adjustment of SLIT liquid preparations as a function of the patient profile and/or treatment response is anchored in clinical practice. Precision dosing might optimize the overall benefit-risk profile of SLIT for individual patients throughout their entire treatment course, enabling them to achieve both short- and long-term treatment goals, whilst maximizing the safety and tolerability.